2019
DOI: 10.1002/eji.201948141
|View full text |Cite
|
Sign up to set email alerts
|

Increased ILC3s associated with higher levels of IL‐1β aggravates inflammatory arthritis in mice lacking phagocytic NADPH oxidase

Abstract: The role of redox regulation in immune-mediated arthritis has been previously described. However, the relationship between innate immune cells, including innate lymphoid cells (ILCs) and phagocyte-derived ROS, in this process remains unclear. Here, we characterize ILCs and measure the IL-1 family cytokines along with other cytokines relevant to ILC functions and development in serum-induced arthritic joints in wild type and phagocytic NADPH oxidase (NOX2)-deficient Ncf1 −/− mice. We found more severe serum-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…A growing body of evidence supports important regulatory roles of leukocytes-derived ROS in inflammatory arthritis ( 21 , 22 , 30 ). In our previous finding, NOX2-deficient mice developed enhanced inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of evidence supports important regulatory roles of leukocytes-derived ROS in inflammatory arthritis ( 21 , 22 , 30 ). In our previous finding, NOX2-deficient mice developed enhanced inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…About 250 µl serum was acquired from each K/BxN mouse, and approximately 2 mL serum was collected from 5-8 K/BxN mice in one batch. Serum was mixed from different batches and 100 µl serum plus 50 µl PBS were injected into one mouse for induction on day 0 and again on day 2 ( 21 , 22 ). Clinical scores were analyzed as the sum of the four limbs, and which would be given a score of 0-3 per limb.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…En la EGC la mayor producción de IL-1b favorece la diferenciación de Tbet+ILC1s a RORγ+ILC3s, lo cual puede contribuir a la iniciación y perpetuación del perfil de inflamatorio. 39 El incremento de los linfocitos TH17 se ha encontrado ligado a la patogénesis de las enfermedades autoinmunes. Se cree que los niveles elevados de linfocitos TH17 e IL-17, IL-21 e IL-23 en EGC podrían participar en la génesis de las enfermedades autoinmunes.…”
Section: El Fenotipo Inflamatorio En Enfermedad Granulomatosa Crónica Por Deficiencia De P40 Phox Y Erosunclassified
“…Thus, the interaction between ILCs and T cells plays an essential role in mounting the most appropriate immune responses against the threat encountered by the individual to maintain homeostasis. However, chronic exposure to environmental stimuli will shift a tissue-protective response into chronic inflammation and pathological injury, in which ILCs were dysregulated or overreacted to some extent [24]. In recent years, it has been reported that ILCs were involved in the pathogenesis of many rheumatic diseases, most of which are characterized by systemic autoimmune responses and persistent uncontrolled inflammation.…”
Section: Ilcs In Homeostasis and Chronic Inflammationmentioning
confidence: 99%